MENGEMBANGKAN SOSIAL EMOSIONAL ANAK USIA DINI MELALUI BERMAIN - Mira Yanti Lubis (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
Playing is an activity that is very important for the growth and development of children. Playing must be done at the initiative of the child and on the decision of the child itself, carried out with pleasure, so that all playful activities will produce a learning process in the child. Playing can also stimulate various children's developments such as physical-motoric, cognitive, logical-mathematical, language, moral-religious, social-emotional and artistic. Through playing, children's creativity will be built up and develop optimally. Children's social-emotional development in principle children learns through social interaction, both with adults and with peers. Social development has a positive impact on children's development. Social development supports communication skills, academic success, and adaptation in schools, and strengthens peer relationships and creates a positive environment in learning. Therefore, this competence must be developed early on optimally. One way to develop emotional social competence in early childhood is through play. Playing can be used as an alternative media in developing social-emotional early childhood